Sources of ammonia for urea synthesis in isolated rat liver cells - Rognstad, Robert (Biochimica et biophysica acta, 1977)
l-Leucine inhibits urea synthesis in rat hepatocytes from a number of nitrogen sources, including ammonia. The inhibition by l-leucine is largely overcome by addition of 1 mM l-ornithine, suggesting that the main site of l-leucine action is at ornithine transcarbamylase, rather than at glutamate dyhydrogenase. l-Norvaline is a more potent inhibitor of urea synthesiss than is l-leucine, but again the inhibition is largely counteracted by l-ornithine. Addition of aminooxyacetate and l-norvaline strongly suppresses the formation of glucose and lactate from l-asparagine, suggesting that an alternate pathway of aspartate metabolism, the purine nucleotide cycle, in not a major pathway. Hadacidin, an inhibitor of adenylosuccinate synthetase, an enzyme of the purine nucleotide cycle, has no effect on urea synthesis in rat liver cells.